Chronic Kidney Disease Predicts Impaired Membrane Microviscosity of Red Blood Cells in Hypertensive and Normotensive Subjects: An Electron Spin Resonance Study - Tsuda, Kazushi (International Heart Journal, 2013)
Current evidence indicates that abnormalities in physical properties of the cell membranes may be strongly linked to hypertension and other circulatory disorders. Recent studies have shown that chronic kidney disease (CKD) might be a risk factor for cardiovascular and cerebrovascular outcomes. The purpose of the present study was to examine the possible relationship between kidney function and membrane fluidity (a reciprocal value of membrane microviscosity) of red blood cells (RBCs) in hypertensive and normotensive subjects using an electron spin resonance (ESR) and spin-labeling method. The order parameter (S) for the ESR spin-label agent (5-nitroxide stearate) in RBC membranes was significantly higher in hypertensive subjects than in normotensive subjects, indicating that membrane fluidity was decreased in hypertension. The order parameter (S) of RBCs was inversely correlated with estimated glomerular filtration rate (eGFR), suggesting that a decreased eGFR value might be associated with reduced membrane fluidity of RBCs. Multivariate regression analysis also demonstrated that, after adjustment for general risk factors, eGFR might be a significant predictor of membrane fluidity of RBCs. The reduced levels of both membrane fluidity of RBCs and eGFR were associated with increased plasma 8-iso-prostaglandin F2α (an index of oxidative stress) and decreased plasma nitric oxide (NO)-metabolites, suggesting that kidney function could be a determinant of membrane microviscosity of RBCs, at least in part, via oxidative stress- and NO-dependent mechanisms. The ESR study suggests that CKD might have a close correlation with impaired rheologic behavior of RBCs and microcirculatory disorders in hypertensive subjects.